1986
DOI: 10.1017/s0022172400066080
|View full text |Cite
|
Sign up to set email alerts
|

Infection with influenza A H1N1: 1. Production and persistence of antibody

Abstract: SUMMARYThree outbreaks of influenza caused by influenza A H1N1 occurred in a boys' boarding school in 1978, 1979 and 1983. The serological response to infection with variants of the H1N1 virus was studied by radial haemolysis and haemagglutination inhibition after primary infection and reinfection. The persistence of this antibody was also studied. Infection in 1978 resulted in the production of persistent antibody to both the haemagglutinin and neuraminidase of the homotypic strain. Antibody which cross-react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The most plausible explanation for this pattern of response is that the primed AI flat children were exposed to the pdmH1N1 strain in the first wave of the pandemic, developed a fully mature AI response after this exposure, and then completely lost their HAI and MN titers in the intervening 7-to 9-month period. Such a rapid loss of antibodies has been reported following both vaccination and natural disease (27,28). Indeed, rapid loss of antibodies appears to be particularly common in young children experiencing their first or second influenza virus infections (27,28).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The most plausible explanation for this pattern of response is that the primed AI flat children were exposed to the pdmH1N1 strain in the first wave of the pandemic, developed a fully mature AI response after this exposure, and then completely lost their HAI and MN titers in the intervening 7-to 9-month period. Such a rapid loss of antibodies has been reported following both vaccination and natural disease (27,28). Indeed, rapid loss of antibodies appears to be particularly common in young children experiencing their first or second influenza virus infections (27,28).…”
Section: Discussionmentioning
confidence: 81%
“…Such a rapid loss of antibodies has been reported following both vaccination and natural disease (27,28). Indeed, rapid loss of antibodies appears to be particularly common in young children experiencing their first or second influenza virus infections (27,28). Although preexisting, cross-reactive antibodies were found in some elderly subjects, presumably due to distant exposure to H1N1 strains circulating in the first part of the 20th century, it seems highly unlikely that the high AI in these children can be explained by cross-reacting antibodies.…”
Section: Discussionmentioning
confidence: 81%
“…A previous study during the reemergence of 1977 H1N1 virus reported detectable levels of antibodies up to 3 years after infection in most children, although kinetics of antibody titer was not reported (4). Reports of the kinetics of antibody responses in serum collected from ill patients seeking medical care during the recent 2009 H1N1 pandemic (A[H1N1] pdm09) have varied between rapid decline within 6 months to maintenance up to 1 year after symptom onset (5)(6)(7).…”
mentioning
confidence: 99%
“…For influenza, it is believed that the longest-lived antibody responses are those generated by infections experienced during childhood, a phenomenon that is referred to as original antigenic sin ( Fazekas De et al, 1966; Lessler et al, 2012 ), and that these antibody responses are detectable at high levels for decades ( Yu et al, 2008 ). The longevity of antibody responses to “non-original” infections is known less well, although our best guess is that that antibody titers stay above the commonly used threshold HI titer of 40 for years ( Horsfall, 1940; Grilli et al, 1986; Severson et al, 2012; Ng et al, 2013 ), as opposed to decades or months. This is likely to depend on strain, age, the degree to which a virus cross-reacts immunologically with other circulating viruses, and whether the estimates come from vaccinees or individuals who were naturally infected.…”
Section: Model and Inferencementioning
confidence: 99%